Anxiety and Family Support During Long-Term EEG Monitoring Among Patients with Epilepsy: A Cross-Sectional Study - Aric Vranada; Dyah Novitaningrum; Warsono Warsono (HealthCare Nursing Journal, 2026)
Patients with epilepsy may experience anxiety during long-term electroencephalography (EEG) monitoring. Family support represents a key psychosocial factor that may influence patients’ psychological responses during this diagnostic procedure. This study aimed to examine the association between family support and anxiety among patients with epilepsy undergoing long-term EEG monitoring. A cross-sectional correlational study was conducted involving 115 patients with epilepsy who underwent long-term EEG monitoring at Dr. Kariadi Hospital, Semarang, Indonesia. Family support was assessed using the Family Support Scale, whereas anxiety was measured using the Hamilton Anxiety Rating Scale. Data were analyzed using Spearman’s rho correlation test. The mean family support score was 40.41, with the majority of respondents reporting moderate levels of family support (52.2%). The mean anxiety score was 24.73, and the majority of respondents experienced moderate levels of anxiety (46.1%). Family support was significantly and negatively correlated with anxiety (r = −0.639, p < 0.001). Family support was significantly associated with anxiety among patients with epilepsy undergoing long-term EEG monitoring. These findings underscore the importance of integrating family-centered nursing interventions to enhance psychological support during diagnostic procedures.